The Development of Learning Package by using Crystal–Based Instructional Model to Enhance Literary Criticism of Undergraduate Student - Naijarun, Khwanchanok (Journal of Education Studies, Chulalongkorn University, 2021)
The current research endeavor aimed to develop learning package centered on the crystal-based instructional model. Another objective of the study was to compare undergraduate students’ capability of literary criticism before and after using the learning package. Lastly, it aimed to study students’ satisfaction with the learning package centered on the crystal-based instructional model. The research procedure consisted of four phases where in phase 1, the focus was on the study of learning and teaching difficulties in the course of literary criticism. Phase 2 comprised of the development of learning package based on the crystal-based approach. In phase 3 there was a trial of the learning package, and phase 4 consisted of the assessment of undergraduate students’ capability of literary criticism and their satisfaction with the learning package. The research sample included 55 students majoring in Thai Language. The research duration was 6 weeks. The research tool was the crystal-based instructional model focusing on learning package and the tools for data collection comprised a literary criticism scale and a satisfaction level scale to assess how satisfied they were with the learning package. Data were analyzed by using mean, standard deviation, and t-test. The results revealed that first, the developed learning package was of the standard efficiency 80/80. Next, students’ capability of literary criticism proved higher after the study than before with the statistical significance of .05. Finally, they showed extreme satisfaction with the learning package.